CLRM-15 TRIAL IN PROGRESS: A PHASE 1B/2 STUDY OF GB5121, A NOVEL, HIGHLY SELECTIVE, POTENT, AND CNS-PENETRANT INHIBITOR OF BRUTON'S TYROSINE KINASE (BTKI) FOR RELAPSED/REFRACTORY PRIMARY/SECONDARY CNS LYMPHOMA (R/R PCNSL/SCNSL) AND PRIMARY VITREORETINAL LYMPHOMA (PVRL). (5th August 2022) - Soussain, Carole; Grommes, Christian; Issa, Samar; Ward, Renee; Peterson, Caryn; Cravets, Matt; Mathias, Anita; Sosa, Judith; Kirby, Brian; Ding, Zhaoqing; Yusuf, Isharat; Rose, Mark; et al.
Abstract: BTK plays an important role in B cell receptor and Toll-like receptor signaling pathways, which are constitutively active in primary CNS lymphomas, and hence represents an excellent therapeutic target. Ibrutinib, a first-generation BTKi, was evaluated in phase 1/2 trials for R/R PCNSL, SCNSL, and PVRL, showing limited survival benefit. GB5121 is a novel, orally available, covalent BTKi with superior specificity, CNS penetration, and CNS target occupancy in preclinical testing versus other BTKis including ibrutinib. GB5121 is well-suited for evaluation in CNS lymphoma. This is a phase 1b/2 open-label study of GB5121 in adults with R/R PCNSL, isolated SCNSL or PVRL and will be conducted in three parts: phase 1b dose-escalation, expansion, and phase 2. Eligibility criteria for phase 1b dose-escalation and expansion (N≈30 for each) include age ≥18 years, ECOG≤2, R/R PCNSL, R/R SCNSL with CNS-only relapse, or R/R PVRL. Patients with newly diagnosed PCNSL who cannot tolerate standard high-dose methotrexate-based therapies are also eligible. Patients with prior allogeneic stem cell transplant are excluded. A Bayesian optimal interval design will be employed to perform dose escalation to determine the recommended phase 2 dose (RP2D). In the absence of dose-limiting toxicity (DLT), dose levels will increase sequentially according to a modified Fibonacci approach. Safety, tolerability, PK/PD, DLT, maximum tolerated dose, and preliminary therapeutic activity will be assessed to determine the optimal biological dose informing the RP2D. Phase 1b expansion will further explore therapeutic activity and characterize safety and tolerability of GB5121 at the RP2D. Phase 2 will initiate following RP2D determination. This is a single-arm, open-label study to investigate GB5121 safety and efficacy in patients with R/R PCNSL. Adverse events will be graded per CTCAE v5.0. Clinical response will be determined using International Primary CNS Lymphoma Collaborative Group criteria. Progression-free and overall survival will be evaluated. Enrollment begins May 2022 (NCT05242146).